The the art of micro frontends build highly scalable, distributed web applications with multiple teams - Rappl, Florian (Packt Publishing Ltd., 2024)
The organizational pattern of micro frontends allows you to split web applications into multiple parts, where each part can be owned by an autonomous team. Each team can have its own development and deployment life cycle, allowing every part of an application to be shipped in isolation. Following the strategies outlined in this book, you can avoid complexity while increasing resilience for your frontend. This updated second edition will guide you through the patterns available to implement a micro frontend solution. You'll learn about micro frontends, the different architecture styles, and their areas of use. Then, you'll learn how to prepare teams for the change to micro frontends, as well as how to adjust the user interface (UI) design and your CSS styles for scalability. Starting with the simplest variants of micro frontend architectures, the book progresses from static approaches to fully dynamic solutions that allow maximum scalability with faster release cycles. In the concluding chapters, you'll strengthen the security level of your micro frontend solution, while reinforcing your overall knowledge with real-world case studies relating to micro frontends. By the end of this book, you'll be able to decide whether and how micro frontends should be implemented to achieve high scalability for your web app.
Includes bibliographical references and index
Keywords: User interfaces (Computer systems); Web site development; Interfaces utilisateurs (Informatique); Sites Web; Développement